'I feel better when…': An analysis of the memory-experience gap for peoples' estimates of the relationship between health behaviours and experiences. Issue 9 (2nd September 2017) - Gloster, Andrew T.; Meyer, Andrea H.; Witthauer, Cornelia; Lieb, Roselind; Mata, Jutta
Abstract : Objective: People often overestimate how strongly behaviours and experiences are related. This memory-experience gap might have important implications for health care settings, which often require people to estimate associations, such as "my mood is better when I exercise". This study examines how subjective correlation estimates between health behaviours and experiences relate to calculated correlations from online reports and whether subjective estimates are associated with engagement in actual health behaviour. Design: Seven-month online study on physical activity, sleep, affect and stress, with 61 online assessments. Main Outcome Measures: University students ( N  = 168) retrospectively estimated correlations between physical activity, sleep, positive affect and stress over the seven-month study period. Results: Correlations between experiences and behaviours (online data) were small ( r  = −.12–.14), estimated correlations moderate ( r  = −.35–.24). Correspondence between calculated and estimated correlations was low. Importantly, estimated correlations of physical activity with stress, positive affect and sleep were associated with actual engagement in physical activity. Conclusion: Estimation accuracy of relations between health behaviours and experiences is low. However, association estimates could be an important predictor of actual health behaviours. This study identifies and quantifies estimation inaccuracies in health behaviours and points towards potential systematic biases in health settings, which might seriously impair intervention efficacy.